PENERAPAN MEDIA GAMBAR BERSERI DALAM MENINGKATKAN BAHASA EKSPRESIF ANAK USIA DINI - Fathor Rozi; Zubaidah (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2021)
This study aims to analyze and examine the application of serial image media to improve expressive language skills of early childhood. The research method used is a descriptive qualitative approach with case studies in class A1 and A2 Kindergarten Al Falah, Kraksaan, Probolinggo. The data collection instruments in this study used direct observation, field notes, and interview notes to support the completeness of the data. The data analysis technique was carried out with the stages of data collection, data reduction, data presentation, and conclusion of research results. The results obtained are serial image media can train children in conveying ideas in good and correct sentence structures. Meanwhile, the implication of the research shows that by utilizing the media of picture series, the improvement of expressive language skills of students in grades A1 and A2 requires a lot of stimulation and opportunities to practice.